1992
DOI: 10.1002/ajh.2830410108
|View full text |Cite
|
Sign up to set email alerts
|

Allogeneic bone marrow transplantation for hematological malignancies following etoposide, cyclophosphamide, and fractionated total body irradiation

Abstract: Forty-three patients received etoposide, cyclophosphamide, and fractionated total body irradiation before allogeneic marrow transplantation. Fifteen patients had chronic myelogenous leukemia in chronic phase or acute leukemia in first remission (standard risk) and twenty-eight patients with more advanced disease (high risk). All patients received etoposide 1,500 mg/m2 intravenously on day -8, cyclophosphamide 60 mg/kg/day intravenously on days -7 and -6, and total body irradiation at 170 cGy twice a day on day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

1994
1994
2008
2008

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…Finally, TBI-VP-16-CY has been effective for autologous stem cell transplantation for pediatric ALL. 16 However, Brown et al, 6 Giralt et al 7 and Yau et al, 8 in non-randomized clinical studies of adults with acute leukemia undergoing allogeneic bone marrow transplantation, all observed relatively high rates of regimen-related toxicity and no apparent advantage of TBI-VP16-Cy over TBI-Cy or other regimens employed in allogeneic transplantation for acute leukemia. In contrast, the results of this study demonstrate that in children, TBI-VP16-Cy is a safe and effective regimen.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, TBI-VP-16-CY has been effective for autologous stem cell transplantation for pediatric ALL. 16 However, Brown et al, 6 Giralt et al 7 and Yau et al, 8 in non-randomized clinical studies of adults with acute leukemia undergoing allogeneic bone marrow transplantation, all observed relatively high rates of regimen-related toxicity and no apparent advantage of TBI-VP16-Cy over TBI-Cy or other regimens employed in allogeneic transplantation for acute leukemia. In contrast, the results of this study demonstrate that in children, TBI-VP16-Cy is a safe and effective regimen.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, in all three aforementioned adult studies, toxicity and in particular, pulmonary toxicity, was a major problem. Giralt et al 7 and Yau et al 8 reported incidences of diffuse alveolar hemorrhage causing death of 8% and 7%, respectively. The lower toxicity rates observed in the present study and in the Horstmann et al 17 study are likely partly attributable to the younger age of the patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, previous reports noted high rates of regimen-related toxicity in adult patients with advanced disease who received intensified conditioning. 49,50 A randomised trial comparing the effectiveness of 12 with 15.75 Gy in patients with AML in CR1 concluded that the higher TBI dose resulted in a decreased relapse rate but in an increase in TRM, and therefore, had no positive impact on EFS. 51 Major ABO incompatibility appeared as a risk factor for chronic GvHD and TRM on multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Although combination of TBI with VP-16 and CY as conditioning regimens has been reported to be effective for patients with hematological malignancies undergoing allogeneic HSCT [14][15][16][17][18], the dose of VP-16, CY, and TBI has been widely varied and no report clearly described the cardiotoxicity of these regimens. On the other hand, some reports on VP-16 (60 mg/kg) and TBI (12 Gy) (VP/TBI) suggested that VP/TBI might increase the risk of graft rejection.…”
Section: Discussionmentioning
confidence: 99%